Tingkat Kepatuhan Pengendara Sepeda Motor terhadap Lampu Lalu Lintas di Simpang Bersinyal (Studi Kasus Simpang Tabek Gadang Pekanbaru) - Halimah Tusaddiah; Edi Yusuf Adiman; Elianora (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2023)
The existence of traffic lights plays an important role in regulating traffic to reduce congestion and the number of accidents. One of the traffic violations committed by motorists is a violation of traffic lights. This study aims to determine the condition of traffic lights and determine the level of compliance of motorcyclists at the Tabek Gadang Intersection. The method used is descriptive analysis. Data collection was carried out by direct observation for one week at 09.00-11.00 and 16.00-18.00. From the results of this study, it can be concluded that the condition of the traffic lights at Simpang Tabek Gadang that are still functioning are red and green. The lamp cycle time for each phase is 137 seconds. The total number of motorcycle riders who passed the Gadang Tabek intersection during the observation period was 107,517 vehicles, 88,336 compliant drivers with a percentage of 82.2% and 19,181 non-compliant vehicles with a percentage of 17.8%. Based on the day of observation, the highest compliance occurred on weekdays at 09.00-11.00 with the very compliant category of 85.1%. Meanwhile on the dayweekend highest adherence at 09.00-11.00 at 83.7%. Based on the highest compliance arm occurred in the HR. Soebrantas Barat arm of 86.9%.